Desutterella n. gen., a new genus of Luzarinae (Orthoptera: Grylloidea: Phalangopsidae) and the first report of the Aracambiae group Souza-Dias & Desutter-Grandcolas, 2014 in the Amazon - Souza-Dias, Pedro G. B.; Campos, Lucas Denadai De; Mello, Francisco De Assis Ganeo De (Zootaxa, 2017)
A new genus and two new species of Luzarinae cricket (Grylloidea, Phalangopsidae) are described from the Amazon Rainforest of Brazil and Colombia. Desutterella manauara n. gen. n. sp. and D. colombiana n. gen. n. sp. are described based in characters of external morphology and genitalia. The new genus is characterized by the presence of reduced and pubescent male forewings, with stridulatory vein visible but other areas for sound production and propagation absent, and file teeth very reduced, vestigial. Regarding the male genitalia, Desutterella n. gen. presents an extra projection in the pseudepiphallic paramere 2, a condition not observed in the Aracambiae until now. Besides the description, we provide morphological evidence for the glandular nature of the metanotum of males through scanning electron microscopy analysis, a discussion about the morphological and genital features of this new genus, and a distribution map of the Aracambiae group.